1994
DOI: 10.1128/jb.176.21.6730-6737.1994
|View full text |Cite
|
Sign up to set email alerts
|

The phage lambda orf gene encodes a trans-acting factor that suppresses Escherichia coli recO, recR, and recF mutations for recombination of lambda but not of E. coli

Abstract: Bacteriophage X can recombine in recBC sbcB sbcC mutant cells by using its own gene orj; the Escherichia coli recO, recR, and recF genes, or both. Expression of an orf-containing plasmid complements the recombination defects of orf mutant phage. However, this clone does not complement a recO mutation for conjugational recombination or recO, recR, or recF mutations for repair of UV-induced DNA damage. A plasmid clone of orf produces a protein with an apparent molecular mass of 15 kDa.Recombination in an Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 49 publications
0
23
1
2
Order By: Relevance
“…These findings are superficially inconsistent with those of a previous study, which suggested a more limited capability of Orf to substitute for RecORF (34). However, in the previous study, orf was expressed from a plasmid.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These findings are superficially inconsistent with those of a previous study, which suggested a more limited capability of Orf to substitute for RecORF (34). However, in the previous study, orf was expressed from a plasmid.…”
Section: Discussioncontrasting
confidence: 56%
“…Orf is deleterious to E. coli, as previously noted by Sawitzke and Stahl (34). Expression of the orf gene from a multicopy plasmid (a pBR322 derivative) directed by the moderate, lac repressor-controllable promoter P mac was found to be lethal to wild-type E. coli, even in a strain bearing FЈ lacI Q .…”
Section: Resultsmentioning
confidence: 75%
“…Results presented above do not distinguish which proteins encoded by nin genes contribute to complementation of the recombination defects of mutant strains lacking RecFOR or RuvC. However, research by others on orf and rap strongly suggests that these are the relevant functions (11,26,28). The mechanism shown in Fig.…”
mentioning
confidence: 96%
“…Two genes in the nin region of phage , orf and rap, function in homologous recombination. The orf gene can substitute for recF, recO, and recR in phage recombination mediated by the host system in recBC sbcBC cells in the absence of the Red system (26). The rap gene encodes an endonuclease which specifically cleaves branched DNA structures, including Holliday junctions, that are thought to be generated during recombination and which hypothetically might substitute for RuvC (11,28).…”
mentioning
confidence: 99%
“…In vitro, the same RecA441 (previously tif; E38K, I298V) and RecA803 (V37M) proteins exhibit an enhanced capacity to displace SSB and bind ssDNA (40,41). In addition, a gene in bacteriophage called ninB or orf (described further below) has been identified that can replace recF, recO, and recR functions in lambda recombination (42,43). In vivo, mutant bacteria missing any of the recFOR functions exhibit a delayed activation of the SOS response that might reflect slow formation of the RecA filaments required to facilitate LexA cleavage (44,45).…”
mentioning
confidence: 99%